Importance of medication reconciliation in cancer patients - Ali Elbeddini; Anthony To; Yasamin Tayefehchamani; Cindy Xin Wen (Taylor & Francis Group, 2021)
Cancer patients are a complex and vulnerable population whose medication history is often extensive. Medication reconciliations in this population are especially essential, since medication discrepancies can lead to dire outcomes. This commentary aims to describe the significance of conducting medication reconciliations in this often-forgotten patient population. We discuss additional clinical interventions that can arise during this process as well. Medication reconciliations provide the opportunity to identify and prevent drug-drug and herb-drug interactions. They also provide an opportunity to appropriately adjust chemotherapy dosing according to renal and hepatic function. Finally, reconciling medications can also provide an opportunity to identify and deprescribe inappropriate medications. While clinical impact appears evident in this landscape, evidence of economic impact is lacking. As more cancer patients are prescribed a combination of oral chemotherapies, intravenous chemotherapies and non-anticancer medications, future studies should evaluate the advantages of conducting medication reconciliations in these patient populations across multiple care settings.